KEWAJIBAN PEGAWAI NEGERI SIPIL MEMILIKI NOMOR POKOK WAJIB PAJAK (NPWP) - Sri Hartini (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Public servant represent one of is one of the tax subject, the public servant must have NPWP. The criterion for officer to make the NPWP minimum of faction is II A and officer of private sector that have income 1,1 million rupiah’s. Tax is foreign exchange of the country. Because of Public servant considered to be a dominant taxpayer, so Public servant obliged to have the NPWP. NPWP is an registration form that given by Office of tax service to the personal people or company that registering it’s self to be confirmed as taxpayer which is used as identification or identity of taxpayer. As administration tool’s, NPWP is important and useful for taxpayer and Office of tax service, so office of tax service try gift NPWP that can be conducted by easily and modestly. If the data have complete, so the NPWP can did only on thirty minute . For public servant that do not execute this rule, it will be considered to be collision discipline of public servant ( PP. No. 30 Year 1980) Kata kunci : kewajiban PNS memiliki NPWP